Comparative and Familial Analysis of Handedness in Great Apes. [article]. - Hopkins, William D.
Historically, population-level handedness has been considered a hallmark of human evolution. Whether nonhuman primates exhibit population -level handedness remaims a topic of considerable debate. This paper summarizes published data on handedness in great apes. Comparative analysis indicated that chimpanzees and bonobos show population-level handedness, whereas gorillas and orangutans do not. All apes species showed evidence of population-level handedness when considering specific tasks. Familial analysis in chimpanzees indicated that offspring and maternal (but not paternal) handedness was significantly positively correlated, but this finding was contingent upon the classification criteria used to evaluate hand prefrences. Overall, the proportion of right handedness is lower in great apes compared with humans, and various methodological and theoretical explanations for this discrepancy are discussed. -- (from the author)